2018
DOI: 10.1080/14767058.2018.1480603
|View full text |Cite
|
Sign up to set email alerts
|

Thiol-disulfide homoestasis in pregnancies with fetal growth restriction

Abstract: The balance of thiol-disulfide homeostasis was shifted and native and total thiol levels were decreased only in preeclamptic FGR pregnancies. The serum disulfide level was increased in idiopathic FGR pregnancies compare to preeclamptic FGR pregnancies which may be a sign of oxidative stress in idiopathic FGR pregnancies with normal thiol pool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Cetin et al [14] compared the thiol-disulfide homeostasis between pregnancies with IUGR and a control group of healthy, pregnant women in their study and reported that total thiol and native thiol levels were low, but disulfide levels were the same as compared to the control group. Cakar et al [13] conducted a study to compare the total thiol, native thiol, disulfide, native thiol/total thiol, disulfide/native thiol, and disulfide/total thiol values in pregnancies with IUGR with a group of healthy, pregnant women. They divided the group of pregnant women with IUGR into two subgroups, i.e., the group with idiopathic IUGR and the group with IUGR coexisting with preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cetin et al [14] compared the thiol-disulfide homeostasis between pregnancies with IUGR and a control group of healthy, pregnant women in their study and reported that total thiol and native thiol levels were low, but disulfide levels were the same as compared to the control group. Cakar et al [13] conducted a study to compare the total thiol, native thiol, disulfide, native thiol/total thiol, disulfide/native thiol, and disulfide/total thiol values in pregnancies with IUGR with a group of healthy, pregnant women. They divided the group of pregnant women with IUGR into two subgroups, i.e., the group with idiopathic IUGR and the group with IUGR coexisting with preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant enzymes, including their activity and overall levels, and the total oxidant or antioxidant status have been studied previously [13,14]. However, serum U-II levels and markers of the antioxidant system have not previously been investigated in the same patients at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress is related to many diseases and the thiolmediated antioxidant system was found to be weakened in obstetric complications such as fetal growth retardation, preeclampsia, premature ovarian failure, hyperemesis gravidarum (16)(17)(18). Antioxidant effect and thiol, which is a part of cysteine amino acid, play a significant role in preventing oxidative stress in the cell (19).…”
Section: Discussionmentioning
confidence: 99%
“…Preservation of antioxidant balance and oxidative stress are important for a variety of benign and malignant conditions such as diabetes mellitus and the familial Mediterranean fever as well as for uterine fibroids (16,(29)(30)(31). Relationship between oxidative stress and uterine fibroids was demonstrated in studies regarding surgically removed leiomyomas and found clear interaction between mainly by lipid peroxidation and leiomyoma (32).…”
Section: Inhibition Of Oxidative Stress In the Cell By Amino Acids Anmentioning
confidence: 99%
“…In the literature, there are studies evaluating the levels of TDH and IMA in pregnancy complications such as gestational diabetes, hyperemesis gravidarum, PE, and intrauterine growth retardation ( 9 , 15 , 16 , 17 ) . Because PE remains an important obstetric complication, there have been ongoing studies on the biochemical markers for the early detection of this disease.…”
Section: Introductionmentioning
confidence: 99%